Development of transplant-acquired multiple food allergies: a case series - Dikici, Ümmügülsüm; Melek Arsoy, Hacer Efnan; Özdemir, Öner (Alergologia Polska - Polish Journal of Allergology, 2025)
Organ transplantation is a life-saving procedure that is widely used in autoimmune diseases, malignancies and organ failures. However, it can bring many complications such as less known and newly described ones e.g. transplant-acquired food allergy (TAFA). Although the causes of TAFA have not been fully elucidated yet, different mechanisms are involved in the pathogenesis, especially the effects of the transplanted liver on the host immune system, and the characteristics of the host, especially drugs that are frequently used in pediatric transplant recipients, such as tacrolimus. In this case series, we present our 3 patients who underwent liver transplantation and developed transplant-acquired multiple food allergies 9–28 months later.